2014
DOI: 10.1371/journal.pone.0091865
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus M2-2 Protein Inhibits Innate Immune Response in Monocyte-Derived Dendritic Cells

Abstract: Human metapneumovirus (hMPV) is a leading cause of lower respiratory infection in young children, the elderly and immunocompromised patients. Repeated hMPV infections occur throughout life. However, immune evasion mechanisms of hMPV infection are largely unknown. Recently, our group has demonstrated that hMPV M2-2 protein, an important virulence factor, contributes to immune evasion in airway epithelial cells by targeting the mitochondrial antiviral-signaling protein (MAVS). Whether M2-2 regulates the innate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Human metapneumovirus (hMPV), the first and only identified human pathogen belonging to the genus Metapneumovirus in the Paramyxoviridae family, is a leading cause of lower respiratory tract disease in children, the elderly, and immunocompromised patients worldwide (Williams et al, 2006;Falsey et al, 2003;Englund et al, 2006). It encodes nine proteins, among which phosphoprotein P, glycoprotein G, small hydrophobic protein SH and the M2-2 protein have been characterized with immune regulatory functions (Bao et al, 2008a(Bao et al, , 2008bKolli et al, 2011;Goutagny et al, 2010;Ren et al, 2012Ren et al, , 2014. In this study, we focused on molecular mechanisms underlying the immune regulatory functions of M2-2 as it was identified with such a function most recently, however with regulatory mechanism largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Human metapneumovirus (hMPV), the first and only identified human pathogen belonging to the genus Metapneumovirus in the Paramyxoviridae family, is a leading cause of lower respiratory tract disease in children, the elderly, and immunocompromised patients worldwide (Williams et al, 2006;Falsey et al, 2003;Englund et al, 2006). It encodes nine proteins, among which phosphoprotein P, glycoprotein G, small hydrophobic protein SH and the M2-2 protein have been characterized with immune regulatory functions (Bao et al, 2008a(Bao et al, , 2008bKolli et al, 2011;Goutagny et al, 2010;Ren et al, 2012Ren et al, , 2014. In this study, we focused on molecular mechanisms underlying the immune regulatory functions of M2-2 as it was identified with such a function most recently, however with regulatory mechanism largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the structural encoding proteins of HMPV—glycoprotein G and M2-2—seem to play a critical role in modulating antiviral IFN production during HMPV infections (2628) as demonstrated by the observation that a mutated HMPV virus lacking glycoprotein G and M2 protein induces significantly higher amounts of IFN and antiviral cytokines/chemokines than wild-type HMPV (27). HMPV also appears to interfere with the activation of the IFN signaling cascade at different points, including Jak1, Tyk2, and IFNAR1 membrane expression (29), all of which may lead to downstream inhibition of STAT1 and STAT2 (13,29).…”
Section: Discussionmentioning
confidence: 99%
“…For M2-2 protein, we and others found that it is a protein with multiple functions. It not only regulates viral gene transcription and viral RNA replication Ren et al, 2012), but also contains a CTL epitope and targets central adaptors for retinoic acid-inducible gene I (RIG-I) and Toll-like receptors (TLRs) (Herd et al, 2006;Kitagawa et al, 2010;Ren et al, 2012Ren et al, , 2014. In addition, M2-2 also plays a significant role in regulating the expression of miRNAs, some of which are important for the expression of immune related genes (Deng et al, 2014).…”
Section: Sliligittlmentioning
confidence: 99%
“…Whether hMPV M2-2 is a key regulatory factor involved in the switch of the viral RNA polymerase from viral gene transcription to viral genome replication, as with the RSV M2-2 protein, is still controversial Kitagawa et al, 2010;Ren et al, 2012). The phosphoprotein P, glycoprotein G, small hydrophobic protein SH and M2-2 protein have all been shown to modulate host immune responses (Bao et al, 2008a, b;Goutagny et al, 2010;Ren et al, 2012Ren et al, , 2014. Recombinant hMPVs, lacking G, SH and M-2, individually or in combination, or having P replaced with avian P, are attenuated Pham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%